Effects of replacing soybean meal with cottonseed meal on growth performance, carcass trait, intestinal development and intestinal microbiota of broiler chickens - Lei Yan; Sha An; Xiaoguo Lv; Zunzhou Lv; Beibei Zhang; Mingan Choct; Yuming Guo; Zhengguo Wang; Baozuo Yan; Yong Li (Poultry Science)
This experiment was conducted to evaluate the effects of replacing soybean meal (SBM) with cottonseed meal (CSM) on growth performance, carcass trait, intestinal development and intestinal microbiota of broilers. A total of 792 one-day-old male Ross 308 broiler chickens were randomly allotted to three treatment groups, with 8 replicates per group and 33 birds per replicate. The control birds were administered a diet consisting primarily of corn and soybean meal. The two treatment groups were fed a similar diet with the soybean meal partially substituted by 5 % (5 % CSM group) or 10 % cottonseed meal (10 % CSM group). The experiment lasted 37 days.Results showed that in the starter phase, the 10 % CSM group had a higher feed conversion ratio (FCR) and a lower average daily feed intake (ADFI) compared to the control group and the 5 % CSM group (P < 0.05). Notably, the 10 % CSM group had the lowest body weight (BW) at 15 days of age (P < 0.05) among all treatments. In the grower phase, there were no significant differences in BW, average daily gain (ADG), and FCR of broilers among all groups (P > 0.05). In the finisher phase, both the 5 % and 10 % CSM groups significantly decreased ADG, and the 10 % CSM group significantly decreased ADFI (P < 0.05). There were no significant differences in final body weight, ADG and ADFI among treatments from 1 to 37 days (P > 0.05). No significant effect of CSM was observed on the slaughter performance of broiler chickens. Compared with the basal diet, 5 % CSM significantly decreased the weight/length index of broiler ileum and the relative weight of duodenum and jejunum at both levels (P < 0.05). Moreover, 5 % and 10 % CSM significantly decreased breast meat pH in 24 h (P < 0.05). Cottonseed meal had no significant effect on the alpha diversity, beta diversity, and taxonomic composition at the phylum and genus levels of the ileal microbiota in broilers (P > 0.05). However, Spearman correlation analysis revealed a strong correlation (P < 0.05) between several bacterial phyla (genera) and the growth performance as well as slaughter performance of broilers.In conclusion, the effect of replacing SBM with CSM in broiler diet on growth performance of broilers varied at different ages. Thus, incorporating 10 % CSM resulted in decreased growth performance during the starter phase, while both 5 % and 10 % CSM levels had similar negative effects during the grower phase. In the finisher stage, the use of 5 % CSM influenced gut weight and meat pH but had no influence on slaughter performance, intestinal health and ileal flora structure of broilers.